Modeling particle deposition in the Balb/c mouse respiratory tract. (20th March 2016) - Winkler-Heil, Renate; Hofmann, Werner
Abstract: The mouse lung has become increasingly important as a surrogate of the human lung for inhalation risk assessment. The main structural difference between the two lungs is that the airway branching of the human lung is relatively symmetric, while that of the mouse lung is distinctly asymmetric or monopodial. The objectives of this study were to develop a stochastic, asymmetric particle deposition model for the Balb/c mouse and to compare predicted deposition patterns with those in the human lung. The asymmetric bronchial airway geometry of the Balb/c mouse was based on a statistical analysis of several lung casts, while, in the absence of pertinent data, the asymmetric acinar airway geometry was represented by an allometrically scaled-down version of the rat acinar region, assuming structural similarity. Deposition of inhaled particles in nasal, bronchial and acinar airways for mouse-specific breathing conditions was computed with the Monte Carlo deposition model IDEAL-mouse. While total deposition for submicron particles decreases with increasing diameter in a fashion similar to that in the human lung, the effect of inhalability and nasal pre-filtration significantly reduces total deposition in the mouse lung for particles with diameters greater than about 3 μm. The most notable difference between submicron particle deposition in the mouse and human airways is the shift of the deposition distribution from distal airway generations in the human lung to upper airway generations in the mouse lung. However, if plotted as a function of airway diameter, both deposition distributions are quite similar, indicating that airway diameter may be a more appropriate morphometric parameter for extrapolation purposes than airway generation.